EDUKASI PROTOKOL KESEHATAN PENCEGAHAN COVID-19 DI ERA NEW NORMAL PADA UMKM DESA PATUGURAN DI KABUPATEN PASURUAN - Bambang Sutikno; Sri Hastari; Yufenti Oktafia (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic is a global reality that affects the fabric of all human life from all levels and attacks anyone who can be infected, and is a common threat that must be prevented by breaking its life cycle. Problems related to the application of health protocols in efforts to prevent Covid-19 such as indiscipline in implementing health protocols, ignoring calls to wear masks when doing activities outside the home are still being ignored. In the current situation and conditions, public awareness to be obedient and obedient in implementing health protocols has an important role as an effort to reduce the number of Covid-19 cases. This activity is a community service activity that is integrated with the Village Development activities of the Faculty of Economics, Universitas Merdeka Pasuruan related to efforts to make residents independent in the era of the Covid-19 pandemic. The material provided in this education is about the COVID-19 prevention health protocol in the new normal era and how to use hand sanitizers and masks as well as physical distancing. Before the education was carried out, the team conducted information gathering on the extent of public knowledge about Covid-19. Based on extracting information, before being given education, the public did not really understand what to do to prevent COVID-19 and nowadays it is rare to strictly enforce protocols. The community hopes that with re-education, the community can understand and become more aware of the importance of maintaining personal hygiene, diligently washing hands, using the right masks and keeping a distance